Tetrayttrium difluoride disilicate orthosilicate, Y4F2[Si2O7][SiO4] - Marion C. Schäfer; Ingo Hartenbach; Thomas Schleid (Acta crystallographica. Section E, Structure reports online, 2013)
In the crystal structure of Y4F2[Si2O7][SiO4], three fundamental building blocks are present, viz. anionic disilicate and orthosilicate units ([Si2O7]6− and [SiO4]4−) and cationic [F2Y4]10+ entities. The latter are built up by two [FY3]8+ triangles sharing a common edge. The four crystallographically independent Y3+ cations display coordination numbers of eight for one and of seven for the other three cations, provided by oxide and fluoride anions. The overall arrangement of the building blocks can be considered as layer-like parallel to the ac plane.